Discovery of a New Biomarker Pattern for Differential Diagnosis of Acute Ischemic Stroke Using Targeted Metabolomics - Sun, Ruitan; Li, Yan; Cai, Ming; Cao, Yunfeng; Piao, Xiangyu (Frontiers in Neurology, 2019)
Stroke is one of the leading causes of disability all over the world. However, there is still a lack of biomarkers for fast differential diagnosis of acute ischemic stroke (AIS) from vertigo or headache. Using a direct-infusion mass spectrometry method, it was possible to establish an efficient method for AIS differential diagnosis that required few minutes. Thirty-eight clearly diagnosed AIS patients and 46 patients with a main complaint of vertigo were enrolled in this study. There was a total of 58 metabolites that were measured by our targeted metabolomics method, and the data were analyzed by pattern recognition algorithms. As a result, a clear classification between AIS and vertigo patients was achieved. Acylcarnitines are the major discriminating metabolites between the two groups. Arginine and its ratio that is related to urea cycle metabolites, including arginine/ornithine and citrulline/arginine, also accounted for the classification. Interestingly, the levels of these metabolites were also found to be restored among recovering AIS patients (n=11), which indicated that the metabolic alterations are possibly related to AIS development. Based on the characters from the data pattern reorganization, a novel biomarkers pattern was established using a binary logistic model, which contained arginine, arginine/ornithine, vaccenyl carnitine and hydroxylbutyrylcarnitine. This biomarkers pattern achieved an area under the receiver operating characteristic curve of 0.89 for the differential diagnosis of AIS. Considering the efficiency and the diagnostic performance of the biomarker pattern, our method has potential future use for the clinical application.